Networks, [Mis]trust, and Pentecostal Conversion: narratives of divergent pathways among small Black entrepreneurs in Tshwane - De Sousa, Julio F (Department of Sociology, 2014)
This thesis is an exploration of the cultural meanings, practices, and discourse that impinge upon the workings of social capital and trust among small black entrepreneurs. Entrepreneurs need to draw on social networks to get advice and resources to launch and manage a business. The contacts that lead to successful outcomes are their social capital and they are a key component of entrepreneurial networks. Structural economic sociologists tend to emphasise 'structural holes', whereby a social actor who is in a position to bridge two actors with no direct ties to each other can parlay control over information into strategic advantage. Recent sociological literature highlights questions of meaning in networks and brings to the fore concerns with the larger cultural framework within which social networks are embedded. Relational economic sociologists contend that networks can be understood as composed of culturally constituted processes. Studies on the networks of South African entrepreneurs are few and far between, and they seem to suggest that African entrepreneurs don't mobilise social capital as well as their Indian and white counterparts. The research used qualitative approaches, relying on a combination of in-depth open-ended unstructured interviews and prolonged ethnographic immersion which generated rich understandings of entrepreneurs' lived experiences, subjective meanings, and contexts. The findings underscore the cultural contingency of social ties and network structure, suggesting that an entrepreneur's proneness to join particular types of associations and networks, and their ability to generate particular types of social ties and generalised trust has something to do with a range of cultural contingencies. The research devoted special attention to the cultural contingency of religion, bringing to light the entrepreneurial consequences of Pentecostal conversion. These intersect with, and extend far beyond, the networks of small black entrepreneurs, affecting issues at the very heart of entrepreneurship such as risk taking and proactiveness. I borrow the concept of 'cultural holes' to illustrate the contingencies of meaning that shape the networks and the entrepreneurial orientation of small black entrepreneurs and, ultimately, drive their divergent entrepreneurial trajectories. Finally, the study adumbrates a typology of small black entrepreneurs, arguing for the possibility that multiple cultural contingencies may open up alternate understandings of entrepreneurship.